Pengaruh Kepemimpinan Partisipatif Kepala Sekolah dan Empowerment Terhadap Kinerja Guru di SMA Negeri 21 Palembang - Trida Setyorini; Bukman Lian; Muhammad Juliansyah (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
The purpose of this study is to find out and describe the influence of participatory leadership of school principals and empowerment together on performance at SMA Negeri 21 Palembang. This research was conducted by taking place at the State High School 21 Palembang. This research was conducted for 4 months in the 2022/2023 gazal semester which lasted from July 2022 to the end of October 2022. In this study, it used field research (field research) which is of the causality type. The population in this study was all teachers of state high school (SMA) 21 Palembang which amounted to 86 people. The sample was calculated using the Slovin formula and obtained the number of 57 teachers. Data collection techniques use questionnaires/ questionnaires, observations and documentation. Data analysis techniques use data normality tests, homogeneity tests, liniearity tests, simple regression analysis, multiple regression analysis, t-tests, F tests and coefficient of determination tests. This research shows the principal's participative leadership and empowerment influence teacher performance at SMA Negeri 21 Palembang, contributing 99.2%. In conclusion, the principal's participative leadership and empowerment significantly influence teacher performance at SMA Negeri 21 Palembang. Keywords : Participatory Leadership; Principal; Empowement, Teacher Performance